PENGARUH SISTEM PENGGAJIAN, UPAH LEMBUR, DAN INSENTIF FINANSIAL TERHADAP KINERJA KARYAWAN (STUDY KASUS PADA CV. DUA ELANG MAKMUR) - Munawarah, Israfil; Arwansyah, Muhamada (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
The era of globalization has made significant changes, the more developed the times, the more rapid the development of humans who want to go to the modern era and keep up with the times. Human resources (HR) are no exception. The purpose of this study was to determine the effect of payroll system, overtime pay and financial incentives on employee performance on CV. Two Prosperous Eagles. The population in this study was employees on CVs. Two Prosperous Eagles with a sample of 40 people. The research method in this research uses Multiple Linear Regression Analysis, The results of the study based on the results of the coefficient of determination test show that the variables of the payroll system, overtime pay and financial incentives contribute 85.4% to affect employee performance on CV. Two Prosperous Eagles and the remaining 14.6% were influenced by other variables that were not studied in this study. Based on the results of the partial hypothesis test that payroll system variables do not affect employee performance, while overtime pay and financial incentive variables have a positive and significant effect on employee performance on CV. Two Prosperous Eagles.